Answer:
Option: B is the correct answer.
B)
![y=(x-1)(x-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eymtaz8g91wyf1u7cjwzoohr3kfx8r7hcv.png)
Explanation:
From the graph that is provided to us, we see that the graph passes through .
the points (1,0) and (3,0).
This means that the zero of the function are at x=1 and at x=3
Hence, when x=1 then y=f(x)=0
and similarly
at x=3 we have f(x)=0
Now, we will check in each of the given options:
A)
![y=(x+1)(x-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k2ht6yhghelxx6w84xbevd6xl3f0xbi4qx.png)
when x=1 then, we have:
![y=(1+1)(1-3)\\\\\\y=2* -2\\y=-4\\eq 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qikqrveiq2ad8nd4o93f0cz1dgv2vkyoah.png)
Hence, option: B is incorrect.
C)
![y=(x-1)(x+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7d7pc1kmvuvjdyahlq8yhohzt1bdeqkrml.png)
when x=3 then, we have:
![y=(3-1)(3+3)\\\\\\y=2* 6\\y=12\\eq 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iw0oiijvocr5echkf8ftrnxs18w052xmis.png)
Hence, option: C is incorrect.
D)
![y=(x+1)(x+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fokt7roh3zelcocwgftdd2io6eptobq0cg.png)
when x=3 then, we have:
![y=(3+1)(3+3)\\\\\\y=4* 6\\y=24\\eq 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fwpxeclrttah0chywc0gqfh27815ojssh9.png)
Hence, option: D is incorrect.
B)
![y=(x-1)(x-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eymtaz8g91wyf1u7cjwzoohr3kfx8r7hcv.png)
at x=1 and at x=3 we get y=0
Also, the graph of this function matches the given graph.
Hence, the correct answer is option: B